Analysis of the Potential and Effectiveness of Hotel Tax Collection in Makassar City: Findings Indicate Underutilized Potential and Areas for Improvement - Lannai, Darwis (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The aim of this study is to assess the potential and effectiveness of hotel tax collection in Makassar, as well as to evaluate the efforts made by local government in optimizing this potential. This study employs a quantitative data analysis approach. In terms of its objectives and nature, the research is descriptive, utilizing a descriptive data collection procedure. According to Regional Regulation No. 3 of 2012 regarding local taxes in Makassar, hotel tax is levied on the services provided by hotels. The taxable object includes not only the services directly offered by hotels but also ancillary services that enhance convenience and comfort, such as sports and entertainment facilities. To calculate the potential and effectiveness of hotel taxes in Makassar, several related variables were considered, including the number of rooms, average room rates, the number of days in a year, occupancy rates, and the established hotel tax rates set by the government. The findings reveal that the potential for hotel tax collection is substantial. This is reflected in the increasing effectiveness of hotel taxes, which exceeded 100% annually from 2014 to 2018, surpassing the effective threshold of 100%. However, the study also indicates that this potential has not been fully tapped, and there are several areas for improvement regarding hotel tax policies in Makassar.